Pemberdayaan Kampung Wisata Kuliner Pring Koening Bunulrejo Sebagai Wujud Kampung Tematik Khas Kota Malang - Rofieq, Mochammad; Siswati, Aris; Fauzy, Muchammad Riza (Jurnal ABM Mengabdi, 2024)
One of the areas in Malang City where most of the residents are young people who are entrepreneurs in the culinary sector is in RT.02/RW.13, Bunulrejo Village, Blimbing District. The culinary MSME actors in this area formed a forum for joint activities called "Pring Koening Culinary Tourism Village". The problem that occurs is that some MSMEs still manage their businesses conventionally, where the management used is still simple and has not utilized marketing technology optimally. The stages used are brainstorming with MSME actors, identifying the types of culinary products marketed, and providing training to culinary MSME actors in this village. The first is Business Management training, the second is Digital Marketing training, and the third is training to build an Entrepreneur Mindset. From this training, an understanding is gained of the importance of an entrepreneur mindset and managing a business unit with proper management. With this training, MSME actors can separate financial records for business from household finances and utilize websites and marketplaces to market their products online. With additional production equipment, MSME actors can increase their productivity to meet consumer demand. So this will have an impact on business comfort and increase their income